Adaptation timescales of estuarine systems to human interventions - van Maren, D. S.; Colina Alonso, A.; Engels, A.; Vandenbruwaene, W.; de Vet, P. L. M.; Vroom, J.; Wang, Z. B. (Frontiers in Earth Science, 2023)
Many estuaries and tidal basins are strongly influenced by various human interventions (land reclamations, infrastructure development, channel deepening, dredging and disposal of sediments). Such interventions lead to a range of hydrodynamic and morphological responses (a changing channel depth, tidal amplitude and/or suspended sediment concentration). The response time of a system to interventions is determined by the processes driving this change, the size of the system, and the magnitude of the intervention. A quantitative understanding of the response time to an intervention therefore provides important insight into the processes driving the response. In this paper we develop and apply a methodology to estimate the response timescales of human interventions using available morphological and hydraulic data. Fitting an exponential decay function to data with sufficient temporal resolution yields an adaptation timescale (and equilibrium value) of the tidal range and deposited sediment volumes. The method has been applied in the Dutch Wadden Sea, where two large basins were reclaimed and where long-term and detailed bathymetric maps are available. Exponential fitting the morphological data revealed that closure of a very large part of a tidal basin in the Wadden Sea initially led to internal redistribution and import of coarse and fine sediments, and was followed by a phase of extensive redistribution while only fine-grained sediments are imported. Closure of a smaller part of a smaller basin led to shorter response timescales, and these response timescales are also more sensitive to rising mean sea levels or high waters. The method has also been applied to tidal water level observations in the Scheldt and Ems estuaries. Exponential fits to tidal data reveal that adaptation timescales are shortest at the landward limit of dredging. The adaptation time increases in the landward direction because of retrogressive erosion (Scheldt) or lowering of the hydraulic roughness (Ems). The seaward increase in adaptation time is related to the seaward widening of both systems.